Primary Tubulovillous Adenocarcinoma of Renal Pelvis: An Unusual Genitourinary Tumor - Kamlesh Suthar; Aruna Vanikar; Rashmi Patel; Kamal Kanodia (Iranian Society of Pathology, 2018)
Prolonged inflammation or irritation due to renal calculi can induce glandular metaplasia of the urothelium and even malignant neoplasm. Primary adenocarcinoma in pelvicalyceal system is a rare tumor in such patients. Here, a case of carcinoembryonic antigen (CEA) positive primary tubulovillous adenocarcinoma in pelvicalyceal system is reported. A 57-year-old male with right abdominal pain and microscopic hematuria and the history of nephrolithotomy for recurrent renal calculi referred to our center. Radiological findings showed well-defined lobulated mass with calcification in interpolar region of right kidney extending up to pelvicalyceal system along with calculi in pelvicalyceal system and ureter with moderate hydroureteronephrosis. Laparoscopic right radical nephrectomy was performed. Histopathological examination revealed tubulovillous adenocarcinoma of renal pelvicalyceal system with CEA positivity. Patient was asymptomatic and had no recurrence after one and a half years. Primary tubulovillous adenocarcinoma in renal pelvis though rare, is usually associated with intestinal metaplasia of urothelium induced by prolonged chronic inflammation and renal calculi.